Environmental Communication of Baduy Luar Indigenous Resource Management - Salsabila Khaerunisah Muslimah; Dinda Rakhma Fitriani (Faculty of Communication Science | Universitas Pancasila Jakarta, Indonesia, 2025)
This study aims to describe the environmental communication practices of the Outer Baduy indigenous community in managing natural resources through an ethnoecological approach. This research is important because indigenous communities are often overlooked in discussions of sustainable resource management, yet they preserve local wisdom that supports ecological balance. A qualitative method with an ethnological approach was used. Data were collected through field observations, in-depth interviews with indigenous leaders and residents, and documentation, and then analyzed using social construction theory and cultural ecology theory. The findings reveal that the Outer Baduy community implements natural resource management based on local wisdom, including a huma-based agricultural system, pikukuh rules that limit overexploitation, and the use of traditional technology. Environmental communication is carried out orally through deliberation, religious rituals, and the intergenerational transmission of values. These practices form a pattern of ecological adaptation that maintains environmental sustainability while strengthening cultural identity. In conclusion, the environmental communication practices of the Outer Baduy indigenous community play a crucial role in preserving human-nature relationships and provide an ethical ecological framework that can inspire sustainable resource management in the wider community.